"I've Been Silenced for so Long": Relational Engagement and Empowerment in a Digital Storytelling Project With Young Women Exposed to Dating Violence. Issue 1 (18th March 2019) - Martin, Stephanie L.; McLean, Jessica; Brooks, Carolyn; Wood, Karen
Despite decades of research identifying the myriad causes and consequences, young women continue to be exposed to a variety of abuses in their dating relationships. Those who experience such violence often feel shame and isolation and hesitate to reach out for support for fear that their stories will not be heard, respected, or garner appropriate responses. Such abuse often results in grave consequences to well-being and quality of life, with the risk of exposure to one incident of abuse potentially leading to a cycle where young women may be repeatedly drawn to abusive relationships. Finding new ways to expose and disrupt this cycle of abuse in intimate relationships is critical. This article highlights the methods used, specifically an adapted version of digital storytelling as a potential empowerment research methodology with a small group of young women exposed to dating violence. Implementation of this methodology occurred in four phases: providing methodological context, preparing (setting the stage), implementing (constructing and sharing digital stories), and evaluating (experience and impact). Each phase of the methodology is described along with lessons learned to advance the innovative use of digital storytelling in anti-violence research.